2015
DOI: 10.1186/s40001-015-0114-8
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction inhibits ovarian follicle development and follicle loss through activating SIRT1 signaling in mice

Abstract: BackgroundSilent information regulator 2 related enzyme 1 (SIRT1) is one of the key factors in the mechanism of calorie restriction (CR) extending lifespan of animals. The aim of the study is to investigate if CR prolongs ovarian lifespan in mice through activating SIRT1 signaling.MethodsIn the present study, 21 female C57BL/6 mice were divided into three groups: the control (n = 7), CR (n = 7), and SRT1720 (n = 7) groups. After the 26-week treatment, the number of ovarian follicles at each stage was counted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Various studies have focused on extending the reproductive span by chronic caloric restriction. 7,59,60 however, the reproductive capacity was shown to be impaired by a prolonged caloric restriction, resulting in subfertility or even infertility. 7,60 In the present study, TRF increased the number of offspring and successful pregnancies rate in mice fed both the chow diet and high-fat diet ( Figures 2D,G), which was coincident with the greater number of ovarian reservations found in the TRF groups ( Figure 1I).…”
Section: F I G U R Ementioning
confidence: 99%
“…Various studies have focused on extending the reproductive span by chronic caloric restriction. 7,59,60 however, the reproductive capacity was shown to be impaired by a prolonged caloric restriction, resulting in subfertility or even infertility. 7,60 In the present study, TRF increased the number of offspring and successful pregnancies rate in mice fed both the chow diet and high-fat diet ( Figures 2D,G), which was coincident with the greater number of ovarian reservations found in the TRF groups ( Figure 1I).…”
Section: F I G U R Ementioning
confidence: 99%
“…Several studies have reported on the effects of starvation (or calorie restriction) on female reproductive function. The collective findings indicate that calorie restriction may inhibit the activation of PFs as well as follicular development and loss, thus extending ovarian lifespan by suppressing mTOR and activating SIRT1 signaling in adult rats [ 14 , 15 ].…”
mentioning
confidence: 99%
“…These observations indicate that SIRT1, SIRT3, SIRT5, and SIRT6 can be markers of ovarian reserve and ovarian aging. Calorie restriction, which suppresses murine ovarian follicle development, was associated with a reduction in the follicular content of SIRT1 and SIRT6 [16]. Therefore, SIRTs 1, 3, 5, and 6 are potentially useful markers to characterize and to predict ovarian follicular development and related fecundity.…”
Section: The Use Of Sirts As Markers Of Ovarian Cell Statementioning
confidence: 99%
“…Unfortunately, the large-scale practical application of SIRTs in medicine, assisted reproduction, and animal biotechnology is limited by problems in their delivery or in the direct control of their expression via cDNA and small RNA constructs. The less time- and money-consuming approach is to promote SIRTs’ accumulation via caloric restriction [2,16] or mTOR regulators.…”
Section: The Use Of Sirts To Study Control and Treat Ovarian Funmentioning
confidence: 99%
See 1 more Smart Citation